Survey of contagious bovine pleuropneumonia in trade cattle slaughtered at abattoirs in North-central Nigeria (2017)
Contagious bovine pleuropneumonia (CBPP) is one of the most important infectious and contagious disease of cattle in sub-Saharan Africa and whose control is urgently needed. A cross-sectional study was conducted to investigate prevalence of CBPP and associated animal factors that predisposed to the disease in trade cattle slaughtered in Niger State, North-central Nigeria between January and May 2014. A total of 525 trade cattle were selected by systematic sampling approach from five purposively selected central abattoirs in the State. Serum samples were analyzed using c-ELISA and lung lesions determined at post-mortem inspections. The OpenEpi 2.3.1 software was used for statistical analyses. Descriptive and analytical statistics were used to present the results. Associations between animal characteristics (predictor variables) and sero-positivity as well as presence of CBPP lung lesions (outcome variables) were tested using Chi-square tests and likelihood backward logistic regressions. A sero-prevalence of 31.8% (95% CI: 27.93, 35.89) in live cattle before slaughtered was observed. Also, 29.5% (95% CI: 25.74, 33.53) of the slaughtered trade cattle had CBPP lung lesions at post-mortem inspections. Cattle in age group 4–5 years were more likely (OR 2.00; 95% CI: 1.17, 3.39) to be significantly exposed to Mycoplasma mycoides subsp. Mycoides (Mmm) infection. Cows were more likely to be significantly predisposed to Mmm infections. Furthermore, bunaji breeds were more likely (OR 2.26, 95% CI: 1.42, 3.59) to be significantly predisposed to Mmm infections. This study has shown the need to combine more reliable serological tests with post-mortem examinations to improve active surveillance of CBPP in trade cattle. These dual approaches to investigation of CBPP and identification of intrinsic factors predisposing to infection should be institutionalized as elements of epidemio-surveillance and control strategies of the disease in sub-Saharan Africa.